2005
DOI: 10.1556/avet.53.2005.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of L-carnitine against oxidative damage caused by experimental chronic aflatoxicosis in quail (Coturnix coturnix)

Abstract: This study was designed to evaluate the effect of L-carnitine supplementation on the plasma malondialdehyde (MDA) and whole blood reduced glutathione (GSH) concentrations in experimentally-induced chronic aflatoxicosis in quails. For this purpose, a total of 80 quails up to 8 weeks old were divided into four equal groups. Group I served as control, Group II was given L-carnitine at the dose of 200 mg/litre in the drinking water for 60 days, Group III was given 60 µg total aflatoxin/kg diet for 60 days, and Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
1
10
0
2
Order By: Relevance
“…An adverse effect World's Poultry Science Journal, Vol. 67, September 2011 of toxin exposure is oxidative stress and this can be reduced by using LC as a supplement (Citil et al, 2005). Similar effects have been reported by Sener et al (2004) in rats.…”
Section: Use Of Silymarin L-carnitine and Vitaminssupporting
confidence: 57%
“…An adverse effect World's Poultry Science Journal, Vol. 67, September 2011 of toxin exposure is oxidative stress and this can be reduced by using LC as a supplement (Citil et al, 2005). Similar effects have been reported by Sener et al (2004) in rats.…”
Section: Use Of Silymarin L-carnitine and Vitaminssupporting
confidence: 57%
“…Those authors found that there was highly significant reduction of MDA of Japanese quail whose diets supplemented with various levels of L-carnitine. Also, Citil et al (2005) observed reduction of plasma MDA and increase whole blood reduced glutathione of Japanese quail supplemented with 200 mg kgG 1 L-carnitine in drinking water. Arockia Rani and Panneerselvam (2001) suggested that the increase of reduced glutathione may be due to the decrease of lipid peroxidation caused by L-carnitine supplementation.…”
Section: Growth -----------------------------------------------------mentioning
confidence: 78%
“…Antioxidant activity and lipid peroxidation: Citil et al (2005) postulated that lipid peroxidation is an indicator of cell damage caused by toxic effects, ageing and stress. The induction of lipid peroxidation gave rise to an increase in MDA content.…”
Section: Growth -----------------------------------------------------mentioning
confidence: 99%
“…L-carnitine or/and coenzyme Q 10 (prior to CCl 4 injection) significantly decreased hepatic LPO level. Citil et al [11] suggested that L-carnitine brought about the inhibition of lipid peroxidation by enhancing antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%